Trends in Terahertz Technology (IntechOpen, 2024)
Terahertz (THz) science deals with the physics, technology, and application of the last unexplored region of the electromagnetic spectrum. The THz region (located between 0.1 and 10 THz) fosters a vast range of sensing for applications in different fields, such as astronomy, non-destructive characterization of materials, communications, defense and security, medicine, and more. This book contributes to three of the main research areas of THz science: THz time-domain spectroscopy, which is the backbone of materials analysis using THz radiation, the use of new 2D materials to develop future THz technology, and the interaction between THz radiation and biology. The contributors to this book are recognized specialists in the THz field.